ISOLASI, KARAKTERISASI DAN PENGELOMPOKAN STRAIN Salmonella typhi ASAL KABUPATEN SUMBA BARAT DAYA NUSA TENGGARA TIMUR BERDASARKAN SIFAT-SIFAT FENOTIP - Charis Amarantini; Langkah Sembiring; Haripurnomo Kushadiwijaya; Widya Asmara (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Typhoid fever is highly endemic in the South-West Sumba Regency, East Nusa Tenggara. The incidence rate of the diseases is high estimated at 725/100,000. It is an acute systemic infection caused by Salmonella typhi. The clinical symptoms of the disease are extremely diverse, starting from the mild form to severe ones with the most feared complication being perforation within the small intestine. Therefore, it is important to perform isolation, characterization, and grouping of S. typhi strains from the blood culture in order to determined definitely diagnosis and the different phenotypic characteristics in the community. Isolation was done in selective and differential media: BacT/ALERT FA culture media, Selenite Cystine Broth, Chromocult Coliform Agar, MacConkey Agar, and Salmonella Shigella Agar. The typical colony of Salmonella was confirmed on Triple Sugar Iron Agar, Urea agar, and L-Lysine decarboxylation media. Phenotypic characteristics of all isolates were identified using API 20E and API 50CHE diagnostics. Based on biochemical characteristics the result showed that 18 strains obtained from different geographical origins were diverse. Four strains have similarity value 100% while the remained strains have similarity value 86.3–98.4%. All of the strains were categorized in the species of S. typhi.